Internal and Marginal Adaptation of Pressable and Computer-Aided Design/Computer-Assisted Manufacture Onlay Restorations - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2012)
The aim of this research was to evaluate internal and marginal adaptation of lithium disilicate partial crowns fabricated using IPS e.max Press and IFS e.max CAD systems. Forty maxillary first molars were divided into two groups. The margins were located above the cementoenamel junction mesially and below it distally. The adaptation of the restoration was evaluated by means of the silicone replica technique. The lowest marginal discrepancy was measured between the preparation margin on the enamel and the IFS e.max Press specimens; the highest discrepancy was observed on the occlusal surface of the IFS e.max CAD specimens. Both systems tested demonstrated acceptable marginal discrepancies in vitro. Int J Prosthodont 2012;25.262-264.
Keywords: IN-VITRO; INTEGRITY